USING OF PLANT TEST SYSTEMS FOR ENVIRONMENTAL CONDITION INDICATIONS OF THE KRYVYI RIH CITY (OVERVIEW) (Ecological Bulletin of Kryvyi Rih District, 2023)
The issue of optimizing the urban environment is of primaryimportance in the modern conditions of the rapid process of urbanization.Plants that are sensitive to environmental pollution and have a quick reactionto the presence of even small doses of toxic substances in the air play animportant role in the system of measures to improve the ecological state ofcities; therefore, they are considered the best indicators of the state of the airenvironment.Usually, the assessment of the state of ecological systems is carried outaccording to various ecological standards and regulations. Among them, themost important are environmental quality standards, which are expressedin indicators of maximum permissible concentrations of harmful substancesin individual environmental objects. Such approaches are based only oninstrumental physico-chemical methods of analysis and are focused onmonitoring compliance with standardized indicators. However, such methodsdo not always timely illustrate the full picture of the impact of pollutantson biota in technogenical-loaded regions, where there is a constant risk ofincreasing the genetic stress of the environment, which is caused to entry intothe ecotopes of pollutants with pronounced mutagenic activity.Therefore, recently a well-founded trend of assessment of the transformedecosystems state traced not only by traditional physicochemical methods, butalso by bioindication methods. Bioindicative methods make it possible todetermine the complex effect of all pollutants present in environmental objects;they are highly sensitive and sufficient for adequate assessments.Long-term studies on the assessment of the Kryvyi Rih city ecological conditionhave reasonable results and its based, as a rule, on the use of standard methods.Bioindication, as an alternative and promising approach in such studies, is notwidespread enough and using very rarely.The article summarizes information about the use of plants in bioindicativestudies of the Kryvyi Rih city. The use of woody and herbaceous plantsin ecological stress determining of the city is compared. The significanceof bioindication for monitoring studies of the city territory is considered.The perspective of using cytogenetic bioindicative studies for the integratedassessment of the environment of the Kryvyi Rih iron ore region is analyzed.
Keywords: bioindication; phytoindication; urban ecosystem; technogenic pollution; monitoring